2013
DOI: 10.3390/nu5061949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Oral Administration of Arachidonic Acid and Docosahexaenoic Acid on the Immune Functions of Young Rats

Abstract: Natural killer (NK) cells have many functional activities, including cytotoxicity and the capacity to produce cytokines and chemokines. NK cell activity is regulated partly by eicosanoids, which are produced from arachidonic acid (ARA) and eicosapentaenoic (EPA) acid. In this study, we investigated the effects of long-term therapy with ARA or docosahexaenoic acid (DHA) on the cytotoxic effects of the NK cells of young rats, which were fed on a nonfish oil diet for two generations. Control oil, ARA (240 mg/kg B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Next we assessed the levels of LPO and ROS as well as inflammatory cytokine levels in plasma; these were not affected by the ARA treatment, suggesting that ARA-administration itself did not cause inflammation and oxidative stress. These results agree with those of our previous study [ 16 ]. Yoshizawa et al reported that an ARA-rich diet for dams during gestation and lactation does not modify N -methyl- N -nitrosourea-induced renal preneoplastic lesions in their offspring [ 25 ], indicating that exogenous free-form ARA does not induce inflammation or oxidative stress in the kidney.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Next we assessed the levels of LPO and ROS as well as inflammatory cytokine levels in plasma; these were not affected by the ARA treatment, suggesting that ARA-administration itself did not cause inflammation and oxidative stress. These results agree with those of our previous study [ 16 ]. Yoshizawa et al reported that an ARA-rich diet for dams during gestation and lactation does not modify N -methyl- N -nitrosourea-induced renal preneoplastic lesions in their offspring [ 25 ], indicating that exogenous free-form ARA does not induce inflammation or oxidative stress in the kidney.…”
Section: Discussionsupporting
confidence: 94%
“…Fatty acid composition in the F-1 diet was described previously [ 15 ]. ARA oil was obtained from Cargill Alking Bioengineering (Wuhan and Hubei, China) [ 16 , 17 ]. The fatty acid compositions of the ARA and control oils are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with a previous study, which showed that n -3 PUFAs increased the levels of IL-10 in mice subjected to Citrobacter rodentium infection [27]. Increased levels of anti-inflammatory cytokines confirmed that n -3 PUFAs could alleviate the systemic inflammatory response induced by injury [28,29,30]. Furthermore, based on previous studies, n -3 PUFAs may also reverse the downregulation of lysozyme and mucin 2 after HSR [21,31,32].…”
Section: Discussionsupporting
confidence: 92%
“…Table 1 shows the fatty acid composition of each dietary oil. The oil administrations were determined as described previously [22]. The G2 young rats (5 weeks old) were randomly divided into three groups: control group, DHA group (the triglyceride form of DHA rich oil: 240 mg/kg BW/day), and ARA group (the triglyceride form of ARA rich oil: 240 mg/kg BW/day).…”
Section: Animalsmentioning
confidence: 99%